2004
DOI: 10.1016/j.euromechflu.2003.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the wakes of two spheres placed side by side

Abstract: The periodic coupled wakes of two spheres, placed side by side in a uniform stream at low Reynolds numbers, are studied experimentally and by Direct Numerical Simulations. Different regimes of interaction are observed, depending on the separation distance between the spheres. For touching spheres, a single wake is found. At small gap sizes, the two wakes interact strongly, and out-of phase shedding occurs. In-phase shedding is observed experimentally for intermediate gap sizes, whereas DNS does not reveal a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…For a single sphere in a uniform flow, when the Reynolds number reaches around 280 and below 360, the plane symmetric hairpin shaped vortices are shed periodically behind the sphere. The orientation of the symmetric plane is arbitrary [29].…”
Section: Flow Past Two Spheres Placed Side By Sidementioning
confidence: 99%
“…For a single sphere in a uniform flow, when the Reynolds number reaches around 280 and below 360, the plane symmetric hairpin shaped vortices are shed periodically behind the sphere. The orientation of the symmetric plane is arbitrary [29].…”
Section: Flow Past Two Spheres Placed Side By Sidementioning
confidence: 99%
“…In early 1980s, some qualitative experimental results for ow past two or three spheres were achieved by Tsuji et al [6]. The latest experimental study about wakes of two spheres placed side-by-side was done by Schouveiler et al [7] and distinctly di erent regimes of interactions were observed, depending on the gap between two spheres.…”
Section: Introductionmentioning
confidence: 97%
“…There are also some experimental works to assess the flow around double sphere arrangements. In another study made by [30] informs about experiments for wake structures of periodic coupled double spheres for Re between 200 and 350. At similar Re numbers, namely at Re 200, flow structure around a leading sphere and a following one was reported [26].…”
Section: Introductionmentioning
confidence: 99%